Retrospective natural history of thymidine kinase 2 deficiency. Issue 8 (30th March 2018) - Garone, Caterina; Taylor, Robert W; Nascimento, Andrés; Poulton, Joanna; Fratter, Carl; Domínguez-González, Cristina; Evans, Julie C; Loos, Mariana; Isohanni, Pirjo; Suomalainen, Anu; Ram, Dipak; Hughes, M Imelda; et al.
Abstract : Background: Thymine kinase 2 (TK2) is a mitochondrial matrix protein encoded in nuclear DNA and phosphorylates the pyrimidine nucleosides: thymidine and deoxycytidine. Autosomal recessive TK2 mutations cause a spectrum of disease from infantile onset to adult onset manifesting primarily as myopathy. Objective: To perform a retrospective natural history study of a large cohort of patients with TK2 deficiency. Methods: The study was conducted by 42 investigators across 31 academic medical centres. Results: We identified 92 patients with genetically confirmed diagnoses of TK2 deficiency: 67 from literature review and 25 unreported cases. Based on clinical and molecular genetics findings, we recognised three phenotypes with divergent survival: (1) infantile-onset myopathy (42.4%) with severe mitochondrial DNA (mtDNA) depletion, frequent neurological involvement and rapid progression to early mortality (median post-onset survival (POS) 1.00, CI 0.58 to 2.33 years); (2) childhood-onset myopathy (40.2%) with mtDNA depletion, moderate-to-severe progression of generalised weakness and median POS at least 13 years; and (3) late-onset myopathy (17.4%) with mild limb weakness at onset and slow progression to respiratory insufficiency with median POS of 23 years. Ophthalmoparesis and facial weakness are frequent in adults. Muscle biopsies show multiple mtDNA deletions often with mtDNA depletion. Conclusions: In TK2 deficiency, age at onset, rate of weakness progression and POS are important variables that define three clinical subtypes. Nervous system involvement often complicates the clinical course of the infantile-onset form while extraocular muscle and facial involvement are characteristic of the late-onset form. Our observations provide essential information for planning future clinical trials in this disorder.